High-dose methotrexate combined with procarbazine and CCNU for primary CNS lymphoma in the elderly: Results of a prospective pilot and phase II study - Illerhaus, G.; Marks, R.; Müller, F.; Ihorst, G.; Feuerhake, F.; Deckert, M.; Ostertag, C.; Finke, Juergen (Annals of Oncology, 2009)
Background: To improve survival of elderly patients with primary central nervous system lymphoma (PCNSL), we conducted a phase II study with high-dose methotrexate (MTX) combined with procarbazine and CCNU. To reduce neurotoxicity, whole-brain irradiation was reserved for patients not responding to chemotherapy. Patients and methods: High-dose MTX was applied on days 1, 15, and 30, procarbazine on days 1-10, and CCNU on day 1. Study treatment comprised up to three 45-day cycles. There was no lower limit of Karnofsky performance status (KPS). Results: Thirty patients with PCNSL (n = 29) or primary ocular lymphoma (n = 1) were included (median age 70 years, range 57-79 years). The median initial KPS was 60% (range 30%-90%). Best documented response in 27 assessable patients were 12 of 27 (44.4%) complete remissions, 7 of 27 (25.9%) partial remissions, and 8 of 27 (29.6%) disease progressions. Two patients died of probable treatment-related causes. With a median follow-up of 78 months (range 34-105), the 5-year overall survival is 33%. Eight of 30 patients (26.7%) are currently alive and well, six without signs of leukoencephalopathy. Conclusion: The combination of high-dose MTX with procarbazine and CCNU is feasible and effective and results in a low rate of leukoencephalopathy. Comorbidity and toxicity remain of concern when treating PCNSL in elderly patients. © The Author 2008. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved.
CRIS-Team Scopus Importer:2024-12-02
Keywords: CNS lymphoma; Elderly; Methotrexate; Neurotoxicity; PCNSL